TOKOH DAN PENOKOHAN DALAM TIGA CERITA PENDEK KALIMANTAN TIMUR: ANALISIS TEORI STRUKTURAL - Yudianti Herawati (Kantor Bahasa Kalimantan Timur, 2019)
The purpose of this study is to describe intrinsic elements of character and characterization using structural analysis in three short stories of East Kalimantan. It discusses about (1) forms of the story, (2) character and characterization distributions, and (3) characters’ personality in